Clinicians’ perceptions of family involvement in the treatment of persons with psychotic disorders: a nested qualitative study - Hestmark, Lars; Romøren, Maria; Hansson, Kristiane Myckland; Heiervang, Kristin Sverdvik; Pedersen, Reidar (Frontiers in Psychiatry, 2023)
Family involvement in mental health care ranges from basic practices to complex interventions such as Family psychoeducation, the latter being a well-documented treatment for psychotic disorders. The aim of this study was to explore clinicians’ perceptions of the benefits and disadvantages of family involvement, including possible mediating factors and processes. Nested in a randomised trial, which purpose was to implement Basic family involvement and support and Family psychoeducation in Norwegian community mental health centres during 2019-2020, this qualitative study is based on eight focus groups with implementation teams and five focus groups with ordinary clinicians. Using a purposive sampling strategy and semi-structured interview guides, focus groups were audio-recorded, transcribed verbatim, and analysed with reflexive thematic analysis. Four main themes were identified as perceived benefits: 1) Family psychoeducation – a concrete framework, 2) Reducing conflict and stress, 3) A triadic understanding, and 4) Being on the same team. Themes 2-4 formed an interconnected triad of mutually reinforcing elements and were further linked to three important clinician-facilitated sub-themes: A space for relatives’ experiences, emotions, and needs; a space for patients and relatives to discuss sensitive topics, and; an open line of communication between clinician and relative. Although far less frequent, three main themes were identified as perceived disadvantages or challenges: 1) Family psychoeducation – occasional poor model fit or difficulties following the framework, 2) Getting more involved than usual, and 3) Relatives as a potentially negative influence – important nonetheless. The findings contribute to the understanding of the beneficial processes and outcomes of family involvement, as well as the critical role of the clinician in achieving these and possible challenges. They could also be used to inform future quantitative research on mediating factors and implementation efforts.